MYCOTOXIN PRODUCTION AND MOLECULAR CHARACTERISATION OF Penicillium SPECIES ISOLATED FROM MILLET GRAINS (Pennisetum glaucum) (L.) R. Br.) IN SOUTHWESTERN NIGERIA (2017)
Millet, a widely consumed food crop, is subject to fungal contamination during storage. These fungi produce mycotoxins in stored food products. Mycotoxins such as citrinin and ochratoxin produced by Penicillium species have been reported to be injurious to consumers. Knowledge of the fungi involved in the production of these mycotoxins will help in the control of its spread in food products. However, there is dearth of information on the mycotoxins produced by Penicillium on millet grain and the species characterisation with molecular technique in Nigeria. Hence, this study was designed to investigate the distribution of Penicillium species and determine the presence of mycotoxins in the millet grains with molecular techniques. Samples of millet grains were purchased from three randomly selected markets each in Lagos, Ogun, Ondo, Oyo and Ekiti states all in southwestern Nigeria. One hundred grains from each of the millet samples were employed for isolation of fungi using Dichloran rose bengal chloramphenicol agar. Morphological identification of the fungal isolates was done using Pitt`s manual. The DNA of the Penicillium species were isolated using standard procedures. Similarities between species were determined by amplifying their internal transcribed spacer (ITS1, ITS4) region and partial beta tubulin gene (Bt2a, Bt2b). Physiological assessment of the Penicillium isolates which includes optimum pH, carbon and nitrogen sources, temperature and incubation time for mycelial growth were carried out using standard methods. Toxigenic screenings of the isolates were carried out by amplifying the genes pksCT, ctnA, orf3 and otanps responsible for citrinin and ochratoxin production. The effects of pH and temperature on mycotoxin production were determined and quantified using Enzyme linked immunosorbent assay. Data were analysed using descriptive statistics. Thirty-four isolates were obtained, out of which twenty-three were identified as Penicillium citrinum (17), P. capsulatum (1), P. simplicissimum (1), P. oxalicum (1), P. steckii (2) and P. chrysogenum (1). Distributions among the states were Ondo: Penicillium citrinum, P. simplicissimum and P. oxalicum, Ogun: Penicillium citrinum and P. chrysogenum while only Penicillium citrinum was obtained from Lagos, Oyo and Ekiti states. Twenty-one isolates showed amplification to the beta tubulin gene with a uniform amplicon size of 500 base pair, while P. simplicissimum and P. oxalicum exhibited variation in amplicon fragement sizes (450 and 550 base pair), respectively. Physiological assessment of the isolates showed optimum growth at pH 8 having 2.51 g Mycelia Weight (MW) and starch as carbon source having (2.14 g MW), (NH4)2SO4 as nitrogen source having (0.86 g MW), optimum temperature was at 30 °C having (0.96 g MW) and 14 days as best incubation time with 0.94 g as dry MW. Toxigenic genes ctnA (678-679 base pair), orf3 (428-447 base pair) and otanps (788 base pair) was detected in six Penicillium (26%) isolates. Ochratoxin production was highest at pH 8 with 7.0 ppb, and at 25 °C with 5.0 ppb. Distribution of Penicillium on millet grain across the study area was determined, the isolates were characterised and mycotoxin from Penicillium citrinum was found to be above the standard permissible limit of ochratoxin.